1983
DOI: 10.1007/bf01848351
|View full text |Cite
|
Sign up to set email alerts
|

The age and nature of Mesozoic-Tertiary magmatism across the Indus Suture Zone in Kashmir and Ladakh (N. W. India and Pakistan)

Abstract: Eine tektonisch ruhige Phase auf der 5rtlichen indischen Kontinentalplatte im Paliioz~n und frtihen Eoz~in wiihrend der Subduktion im asiatischen Randgebiet.Ein weiterer Schub des Indischen Kontinental-Randes nach Siiden in Zusammenhang mit der Bildung eines Anden-~ilmlichen Bogens (des Ladak_h-Deosai-Batholithen) im nSrdlichen indischen Randgebiet ira Eoz~in.Ein oligoz~iner andischer Bogen (die Karakorum-Batholithen) im asiatischen Randgebier, gefolgt yon einer mioziinen KoUision der zwei Kontinente sowie der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Burg (2011b) suggests that the (Kohistan) intra-arc rifting, attributed to trench rollback (Burg et al, 2006;Treloar et al, 1996), may have removed the need for subduction along the southern Karakoram margin as India's faster northward motion i.e., faster subduction of the Tethys, then formed most of the Kohistan Batholith. Continued closure between India and Eurasia resulted in locking of the intervening Kohistan Arc (or KLA) during the Eocene-Miocene (Brookfield and Reynolds, 1981;Reynolds et al, 1983), as convergent thrusting created unconformable Eocene lavas, 30 Ma old plutons, and mainly north-vergent/south-dipping structures in the KKSSZ (Burg, 2011b).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Burg (2011b) suggests that the (Kohistan) intra-arc rifting, attributed to trench rollback (Burg et al, 2006;Treloar et al, 1996), may have removed the need for subduction along the southern Karakoram margin as India's faster northward motion i.e., faster subduction of the Tethys, then formed most of the Kohistan Batholith. Continued closure between India and Eurasia resulted in locking of the intervening Kohistan Arc (or KLA) during the Eocene-Miocene (Brookfield and Reynolds, 1981;Reynolds et al, 1983), as convergent thrusting created unconformable Eocene lavas, 30 Ma old plutons, and mainly north-vergent/south-dipping structures in the KKSSZ (Burg, 2011b).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…These formations could not be traced to the east of Ladakh sector in Lhasa and southern Tibet region and remain a peculiarity of the northwestern Himalaya. However, tectonic models proposing two subduction zones in general assume two sutures along the entire south Asian boundary (Brookfield and Reynolds, 1981;Rai, 1983;Reynolds et al, 1983;Coward and Butler, 1985;Petterson and Windley, 1985;Srimal, 1986;Sharma, 1987;Treloar et al, 1989;Searle et al, 1997;Weinberg and Dunlap, 2000;Dunlap and Wysoczanski, 2002;Robertson and Collins, 2002;Dubois-Cote et al, 2005;Dupuis et al, 2005). This has resulted in various attempts of correlating older sutures present in Lhasa-Tibet block with the Shyok suture (Dunlap and Wysoczanski, 2002;Lacassin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Brookfield and Reynolds (1981), and Reynolds et al (1983) suggested that the Shyok suture closed in Miocene after the Late Cretaceous suturing along the Indus suture. However, Coward and Butler (1985), Petterson and Windley (1985), Treloar et al (1989) and Searle et al (1997) proposed that the Shyok suture is older than the Indus suture.…”
Section: Introductionmentioning
confidence: 99%
“…Brookfield and Reynolds [8] and Reynolds et a1. [9] suggested that the Shyok suture did not close before the Miocene and therefore considered it to be younger than the Indus suture. Srimal [10], however, suggested that the tectonic units accompanying the Shyok ophiolites were part of a collage between the northern margin of India and the southern margin of the Asian plate.…”
Section: Introductionmentioning
confidence: 99%